A Hemilabile and Cooperative N‐Donor‐Functionalized 1, 2, 3‐Triazol‐5‐Ylidene Ligand for Alkyne Hydrothiolation Reactions. Issue 6 (22nd December 2016) - Strydom, Ian; Guisado‐Barrios, Gregorio; Fernández, Israel; Liles, David C.; Peris, Eduardo; Bezuidenhout, Daniela I.
Abstract: A series of novel cationic and neutral Rh complexes with an N‐donor‐functionalized 1, 2, 3‐triazol‐5‐ylidene (TRZ) ligand (in which the pendant N donor is NHBoc, NH2, or NMe2 ) is described. The catalytic activity of these complexes was evaluated in the hydrothiolation of alkynes. Among the catalysts, a neutral dicarbonyl complex featuring the tethered‐NBoc amido‐TRZ ligand proved very selective for alkyne hydrothiolation with an aryl thiol. Remarkably, the reaction could be carried out in the absence of pyridine or base additive. In addition, during the reaction, no evidence for oxidative addition of the thiol S−H bond was observed, strongly suggesting a reaction pathway in which a bifunctional ligand is involved. Experimental and theoretical mechanistic investigations suggest a ligand‐assisted deprotonation of thiol, hemilabile dissociation of amine from the metal, and thiolate coordination, which is indicative of a different reaction mechanism to those previously reported for related alkyne hydrothiolation reactions. Abstract : Cooperation in action ! A ligand‐ assisted acid‐base thiol‐activation strategy is reported for the regioselective hydrothiolation of alkynes mediated by a rhodium(I) catalyst.